1998
DOI: 10.1152/ajpgi.1998.275.4.g789
|View full text |Cite
|
Sign up to set email alerts
|

Reduced folate derivatives are endogenous substrates for cMOAT in rats

Abstract: We examined the role of the canalicular multispecific organic anion transporter (cMOAT) in the biliary excretion of reduced folate derivatives in vivo and in vitro using normal [Sprague-Dawley rats (SDR)] and mutant [Eisai hyperbilirubinemic rats (EHBR)] rats whose cMOAT is hereditarily deficient. In vivo, the biliary excretion of endogenous tetrahydrofolate (H4PteGlu), 5-methyltetrahydrofolate (5-CH3-H4PteGlu), and 5,10-methylenetetrahydrofolate (5,10-CH2-H4PteGlu) in EHBR was reduced to 8.2%, 1.9%, and 5.5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Similar transporters to this OATP-2 were confirmed in the rat liver, OATP-1/4 (3,17). It has been reported that endogenous reduced folate [8], PV [9,18] and methotrexate [11] are the substrate of these transporters. Supposing that rabbits might also have a similar transporter in their liver, we examined the pharmacokinetics of FNX in rabbits using concomitant administration of a large amount of PV, expecting to block possible FNX uptake into the liver cells by means of PV.…”
Section: Discussionsupporting
confidence: 69%
“…Similar transporters to this OATP-2 were confirmed in the rat liver, OATP-1/4 (3,17). It has been reported that endogenous reduced folate [8], PV [9,18] and methotrexate [11] are the substrate of these transporters. Supposing that rabbits might also have a similar transporter in their liver, we examined the pharmacokinetics of FNX in rabbits using concomitant administration of a large amount of PV, expecting to block possible FNX uptake into the liver cells by means of PV.…”
Section: Discussionsupporting
confidence: 69%
“…ATP-dependent MTX transport was also shown to be absent in canalicular membranes prepared from the liver of these animals (Masuda et al, 1997). Subsequent studies established that THF, 5-CH 3 -THF, 5-10-CH 2 -THF, and 10-CHO-THF are also substrates for MRP2 (Kusuhara et al, 1998).…”
Section: Mrps and Their Role In Antifolate Resistancementioning
confidence: 99%
“…Transport across the bile canalicular membrane of many organic anions including glutathione, glucuronide and sulfate conjugates is mediated by an active transporter, a so-called canalicular multispecific organic anion transporter (cMOAT) [3]. Recently, it has been shown that the substrates for cMOAT also include MTX [4] and reduced folate derivatives [5]. There is increasing evidence in the literature of an inducing effect of a variety of cytotoxic, carcinogenic, and chemotherapeutic agents on cMOAT [6].…”
Section: Introductionmentioning
confidence: 99%